Measurment Bank Muamalat's Performance Using Financial Ratios - Novi Fadhila; Irma Christiana (Journal of International Conference Proceedings (JICP), 2019)
This research is quantitative descriptive. The purpose of this study is to analyze the performance of Bank Muamalat using the Financial Ratio in the form of Liquidity, Solvability and Profitability ratios. The object of this research is Bank Muamalat. The type of data used is quantitative data sourced from published financial statements. The results of this study are: Financing to Deposits Ratio is in good condition, Capital Adequacy Ratio is in very good condition, Return On Asset shows bad condition, Return On Equity is in bad condition, Net Interest Margin in 2017 is not healthy and Operating Expenses to Operating Revenues efficiently.